Analisis Strategi Pembangunan Daerah Tertinggal di Aceh Besar - Zulfan Zulfan; Irwan Safwadi; Yuliana Yuliana; Lukman T.Ibrahim; Dewi Astini (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
This study aims to determine the development strategy of disadvantaged areas in Aceh Besar District and the obstacles faced in developing disadvantaged areas in Aceh Besar District. This study uses a descriptive quantitative approach. The population in this study was all the underdeveloped villages in Aceh Besar District as many as 32 villages. The research sample consisted of 2 villages in Montasik District, namely Lampaseh Lhok Village and Weu Bada Village. Data collection with documentation techniques. The data used are in the form of data and archives regarding underdeveloped areas, Bappenas, Ministry of Villages, Bappeda, BPS and other related agencies. The data analysis model is descriptive quantitative and quantitative in the form of SWOT analysis. Based on the results, it is known that there are several development strategies for underdeveloped areas carried out by the Aceh Besar District Government, including the field of Human Resources (HR) development strategies carried out through the education sector by increasing education personnel and increasing the number of educational facilities. In the health sector, increasing medical personnel and health advice such as puskesmas at the sub-district level and posyandu and polindes at the underdeveloped village level with locations that can be reached by all disadvantaged rural communities. In the infrastructure sector, the strategy is to improve the quality of roads in terms of length, width and surface, clean water management, transportation and irrigation by using pumping and piping systems to meet the water needs of farmers. In the economic aspect, the Aceh Besar District government carries out a strategy by prioritizing aspects of people's economic empowerment based on mukim gampong by building the agricultural, fishery, and coastal management sectors into tourist destinations. The strategy for developing social and poverty aspects is carried out by opening up various employment opportunities, in the form of aquaculture, trade, agriculture and animal husbandry. Obstacles to the development strategy for disadvantaged areas of the Aceh Besar Regency government in the form of still strong sectoral egos, the allocation of development funds is not in accordance with the target, the allocation of unsustainable development and the lack of interest in the business world in investing funds or managing disadvantaged areas in Aceh Besar Regency.